Discussion on Sulfur Corrosion and Protection of High Sulfur Crude Oil Processing Equipment - JIANG Chuan-dong, HUANG Wei, CONG Yu-feng, SU Jian, ZHANG Zhe (Cailiao Baohu)
In recent years, the processing proportion of domestic high sulfur crude oil has been increasing gradually.The corrosion of equipment by sulfide in the process of crude oil processing is an urgent problem that should be solved in industry.In this paper, the existing forms of sulfur compounds in high sulfur crude oil were described and the corrosion types of sulfur were analyzed.Protection technology of the common oil processing equipment in recent years were summarized from two aspects: one was for electric desalting of crude oil pretreatment technology, oil demetallization technology, biological desulfurization technology, the other was for equipment protection of chemical protection coating technology, material surface modification and adding corrosion inhibitor technology, especially the research mechanism of new-type corrosion inhibitors was summarized.Finally, the research direction of protection technology for high sulfur crude oil processing equipment in the future was prospected.